Kendali Diri Perilaku Seksual dan Pengembangannya Melalui Konseling pada Siswa Madrasah Aliyah di Kabupaten Bandung - Tajiri, Hajir (IAIN Ponorogo, 2016)
Free sex problems on weakly self-controlled individual starts to afflict Madrasah Aliyah students. This reality should not happen to religious-based school. One of this problem prevention is to develop self-control. This research provides empirical data based on on self-control, especially sexual behavior on students and its handling is through Cognitive Behavioral Therapy (CBT) model. This research was a research and development (R & D). This research process was carried out through the stages of: (1) pre-development and library research; (2) design of hypothetical model; (3) rational model validation; (4) model revision; (5) try out of model; (6) revision of try out; (7) Â dissemination of model. The results of the study indicate that: (1) based on self-control of sexual behavior of MAN Ciparay and MAS Al-Mukhlisin students Â in the year 2009/2010 in Bandung regency, it is said that most of them is potential to practice a free sex or deviation. (2) Cognitive Behavioral Therapy (CBT) model developed to improve self-control of sexual behavior of MAN CiparayÂ and MAS Al-Mukhlisin students in Bandung regency is adequate. The relation between the problem and therapy model is relatively significant or closely related.(3) Model application consists of : identifying problem, grouping students based on their level of self-control, giving treatment.(4) Cognitive Behavioral Therapy (CBT) model is effectively proven ways to improve self-control of sexualÂ behavior of MAN CiparayÂ and MAS Al-Mukhlisin students in Bandung regency. This effectiveness is indicated through the comparation between pre test and post test on experiment group and the result of pre test and post test on control group.Ù Ø´ÙÙØ© Ù Ù Ø§Ø±Ø³Ø© Ø§ÙØ¬ÙØ³ÙØ© Ø§ÙØØ±ÙØ© Ø§ÙÙØ§ÙØ¹Ø© Ø¨Ø³Ø¨Ø¨ Ø¶Ø¹Ù Ø¶Ø¨Ø· Ø§ÙÙÙØ³ Ø¨Ø¯Ø£Øª ØªÙØ¹ ÙÙ ØÙØ§Ø© Ø·ÙØ§Ø¨ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©. ÙÙØ°Ù Ø§ÙØ¸Ø§ÙØ±Ø© ÙØ§ÙØ¬ÙØ² ÙÙÙØ¹ÙØ§ ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¯ÙÙÙØ©. ÙÙØ§ ØªÙÙÙ Ø£ÙÙ ÙØ© Ø§ÙÙ ØØ§ÙÙØ© ÙÙ ÙØ¹ÙØ§ Ø¹Ù Ø·Ø±ÙÙ Ø¶Ø¨Ø· Ø§ÙÙÙØ³. Ø¹Ø±Ø¶ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø§ÙØ¨ÙØ§ÙØ§Øª Ø¹Ù ØµÙØ±Ø© Ø¶Ø¨Ø· Ø§ÙÙÙØ³Ø ÙØ®Ø§ØµØ© Ø¹Ù Ø§ÙØ³ÙÙÙ Ø§ÙØ¬ÙØ³Ù ÙÙØ·ÙØ§Ø¨ ÙÙ ØØ§ÙÙØ© ØÙÙÙ Ø¹Ù Ø·Ø±ÙÙ Ø§ÙØ§Ø±Ø´Ø§Ø¯Ø§Øª ÙÙ Ø§ÙØ¬Ø§ÙØ¨ Ø§ÙÙ Ø¹Ø±ÙÙ-Ø§ÙØ³ÙÙÙÙ.Â ÙØ§ØªÙØ¨Ø¹ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ù ÙÙØ¬ Ø§ÙØ¨ØØ« Ø§ÙØªØ·ÙÙØ±Ù. ÙØ§ØªÙØ®Ø° ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø§ÙØªØ·ÙÙØ±Ù Ø§ÙÙ Ø±Ø§ØÙ : ÙÙ 1) Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙØ£ÙÙÙØ© ÙØ§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙØ«Ø§Ø¦ÙÙØ©Ø 2) ØªØ¹ÙÙÙ ÙÙ Ø· Ø§ÙÙØ±Ø¶ÙØ©Ø 3) ØªØµØ¯ÙÙ Ù Ø¹ÙÙÙÙØ© Ø§ÙÙÙ Ø·Ø 4) ØªØµØÙØ Ø§ÙÙÙ Ø·Ø 5) ØªØ¬Ø±Ø¨Ø© Ø§ÙÙÙ Ø·Ø 6) ØªØµØÙØ ÙØªÙØ¬Ø© ØªØ¬Ø±Ø¨Ø© Ø§ÙÙÙ Ø·Ø 7) Â ØªØ·Ø¨ÙÙ Ø§ÙÙÙ Ø·. ÙÙØªØ§Ø¦Ø ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙØ§ÙØªØ§ÙÙ : 1) Ø¹ÙÙ Ø£Ø³Ø§Ø³ ÙØ¯Ø±Ø© Ø¶Ø¨Ø· Ø§ÙÙÙØ³ Ù Ù Ø§ÙÙ Ù Ø§Ø±Ø³Ø© Ø§ÙØ¬ÙØ³ÙØ© ÙØ§Ù Ø·ÙØ§Ø¨ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØÙÙÙ ÙØ© Ø¬ÙÙØ§Ø±Ø§Ù Ù Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØ£ÙÙÙØ© Ø§ÙÙ Ø±ØÙØ© Ø§ÙØ¯Ø±Ø§Ø³ÙØ© 2009-2010 Ù ÙÙ Ù ÙØ·ÙØ© Ø¨Ø§ÙØ¯ÙÙØ¬ ÙÙ ÙÙ Ø£Ù ÙÙÙØ§Ù Ø£Ù Ù Ø¹Ø¸Ù ÙÙ ÙÙÙ ÙØ±ØµØ© Ù ØªØ§ØØ© ÙÙÙÙØ§Ù Ø¨Ø§ÙØ¹Ù ÙÙØ© Ø§ÙØ¬ÙØ³ÙØ© Ø§ÙØØ±ÙØ©Ø 2) ÙØ§ÙÙÙ Ø· Ø§ÙØ§Ø³ØªØ´Ø§Ø±Ù Ø§ÙÙ Ø¹Ø±ÙÙ-Ø§ÙØ³ÙÙÙÙ Ø§ÙØ°Ù ÙØ§Ù Øª Ø¨Ù Ø§ÙÙ Ø¯Ø±Ø³Ø© ÙØªØ±ÙÙØ© Ø¶Ø¨Ø· Ø§ÙÙÙØ³ ÙÙ ÙÙÙØ³ Ø·ÙØ§Ø¨ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØÙÙÙ ÙØ© Ø¬ÙÙØ§Ø±Ø§Ù ÙØ§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØ£ÙÙÙØ©